2016
DOI: 10.2174/1570159x14666160119094646
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived Neurotrophic Factor (BDNF)-TrkB Signaling in Inflammation-related Depression and Potential Therapeutic Targets

Abstract: Depression is the most prevalent and among the most debilitating of psychiatric disorders. The precise neurobiology of this illness is unknown. Several lines of evidence suggest that peripheral and central inflammation plays a role in depressive symptoms, and that anti-inflammatory drugs can improve depressive symptoms in patients with inflammation-related depression. Signaling via brain-derived neurotrophic factor (BDNF) and its receptor, tropomycin receptor kinase B (TrkB) plays a key role in the pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
229
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 404 publications
(262 citation statements)
references
References 126 publications
8
229
1
3
Order By: Relevance
“…It is well known that LPS can induce sickness behavior that peaks 2 to 6 h after a single administration and then gradually wanes [1,6]. The behavior results from the activation of proinflammatory cytokine signaling in the brain, in response to peripheral LPS injection, and the ensuing depression-like behavior peaks 24 h post-LPS injection [1,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that LPS can induce sickness behavior that peaks 2 to 6 h after a single administration and then gradually wanes [1,6]. The behavior results from the activation of proinflammatory cytokine signaling in the brain, in response to peripheral LPS injection, and the ensuing depression-like behavior peaks 24 h post-LPS injection [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism underlying the pathophysiology of depression is unknown, multiple lines of evidence suggest that inflammation plays a key role in the pathophysiology of depression [1][2][3][4][5][6]. Meta-analyses showed higher blood levels of proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin-6 (IL-6), in drugfree depressed patients, compared with healthy controls [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the role of inflammation in the development of depression [9][10][11], it is possible that sEH contribute to the pathophysiology of this disorder. Recently, Ren et al [12] reported that the sEH inhibitor TPPU (1-(1-propionylpiperidin-4-yl)-3-(4-(trifluoromethoxy)phenyl)urea) conferred prophylactic and antidepressant effects in the inflammation and social defeat stress models of depression.…”
Section: Key Role Of Seh In Depressionmentioning
confidence: 99%
“…pathophysiology of depression and in the antidepressant functions of antidepressants [10][11][12][13][14][15][16][17][18]. Alterations in BDNF-TrkB signaling in the brain have been implicated in the pathogenesis of depression and antidepressant mechanisms.…”
Section: Introductionmentioning
confidence: 99%